2019
DOI: 10.1080/17518423.2019.1645227
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Construct Validity for the Modified Mental Fatigue Scale When Used in Persons with Cerebral Palsy

Abstract: Introduction: Fatigue impacts negatively on everyday activities in individuals with cerebral palsy (CP). More knowledge is needed about how mental fatigue is manifested in this target group. The purpose of this study was to gather evidence about the validity of the modified Mental Fatigue Scale (m-MFS) in adults with CP. Methods: Mixed sequential exploratory design. The respondents were ten persons aged 22-56 with CP (MACS I-II). Results: The respondents perceived the m-MFS as easy to read and understand. Its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The Mental Fatigue Scale (MFS) has been evaluated for people with acquired brain injury ( Johansson et al, 2010 ; Johansson and Rönnbäck, 2014a ). The MFS has also been used in neurological conditions ( Johansson et al, 2010 ; Bergqvist et al, 2019 ), endocrine diseases ( Papakokkinou et al, 2015 ; Holmberg et al, 2021 ) and BO ( Skau et al, 2021 ) and has also shown good correlation with status in the workplace after TBI ( Palm et al, 2017 ). The MFS is a self-assessment form based on extensive clinical research into diseases that affect the brain ( Lindqvist and Malmgren, 1993 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Mental Fatigue Scale (MFS) has been evaluated for people with acquired brain injury ( Johansson et al, 2010 ; Johansson and Rönnbäck, 2014a ). The MFS has also been used in neurological conditions ( Johansson et al, 2010 ; Bergqvist et al, 2019 ), endocrine diseases ( Papakokkinou et al, 2015 ; Holmberg et al, 2021 ) and BO ( Skau et al, 2021 ) and has also shown good correlation with status in the workplace after TBI ( Palm et al, 2017 ). The MFS is a self-assessment form based on extensive clinical research into diseases that affect the brain ( Lindqvist and Malmgren, 1993 ).…”
Section: Methodsmentioning
confidence: 99%
“…In Norway, it is recommended to use instruments for assessment of fatigue, pain, self-care abilities and activities of daily living, as this might affect participation in everyday life and employment. Suggested instruments are the Fatigue Severity Scale (FSS) ( 59 ) or the Modified Mental Fatigue Scale, which is developed particularly for adults with CP ( 60 ), the section on pain from the Short Form Health Survey-36 (SF-36) ( 61 ), and the 12-item version of the World Health Organizations Disability Assessment Schedule 2.0 (WHODAS 2.0) ( 62 ). The FSS, WHODAS 2.0, and pain questions from SF-36 are already part of CPUP for adults in Sweden.…”
Section: Materials and Equipmentmentioning
confidence: 99%
“…Fatigue is most commonly described in the literature within a physical domainfor example, feelings of bodily tiredness, a lack of energy for physical tasks and local muscle fatigue [8] . More infrequently studies report on cognitive or mental fatigue, which describes excessive cognitive tiredness or exhaustion in response to a demanding task or significant sensory stimulation [9] . Such cognitive fatigue is associated with a disproportionally long recovery time and is an atypical or pathological response to a challenging task [9] .…”
Section: Introductionmentioning
confidence: 99%
“…More infrequently studies report on cognitive or mental fatigue, which describes excessive cognitive tiredness or exhaustion in response to a demanding task or significant sensory stimulation [9] . Such cognitive fatigue is associated with a disproportionally long recovery time and is an atypical or pathological response to a challenging task [9] . Physical and cognitive fatigue can be experienced in isolation or together.…”
Section: Introductionmentioning
confidence: 99%